Insects associated with crop plants in and out plastic tunles in Salahaldin Governorate - Ali H. Al-Tikrity; Talib O.Al-Khesraji; Taha H. Jasim (Tikrit Journal of Pure Science, 2023)
The present study was carried out during December 2011-july 2012 in several areas in salah-aldin governorate to provide information on insect fauna associated with some economic field crops under plastic cover and crops after cover removal .The study also aimed to obtain information about the chemistry of plant –insect relationship . A total of 30 insect species from 24 families and 8 orders were collected from the studied crops . more than 30 unidentified insect species in different families and order were also collected from these crops. among collected insects , several insect pests ( ex. Thrips tabaci, Chrysoperla sp, Myzus persicae, Halictus sp, Hypera postica) insect predates ( ex. Orius albidipennis , Sphegigaster orobanchiae) insect pollinators (ex. Anthophora sp, Halictus sp, Andrena sp) and parasitic insects (ex. Aphidius sp ) were reported . It was revealed that some insect species occurred on all studied crops (ex. Myzus persicae, Coccinella punctate and Liorhyssys hyolinus) while other insect species were restricted to members of one ( ex. Aphoidius lividus, and Anthophora sp. on eggplant) or two plant families ( ex. Anthicus sp, Chrysocharis sp. And Cryptus sp on cuecrbitaceae and solanceae ) . some insect species were found only on covered plants ( ex. Cryptus sp, Eucera sp. And Tachys lucasi) whereas others were found dominant only on uncovered plants (ex. Orius albidipennis, Aphidius sp and Sphegigaster orobanchiae). However , several insect species were found on both covered and uncovered crops ( ex. Halictus sp, Myzus persicae and Coccinella punctate).